FORENSIC ACCOUNTING AND FRAUDS - Shilpa Thakur (International Journal For Research In Educational Studies, 2024)
India is leading its way towards attainment, progress and growth with global recognition as one of the fastest growing economies of the contemporary world. This emerging face of India is indeed a capture of spirited government’s reform and initiatives under the realm of Good Governance. The contemporary lead of good governance, which revolves around five ‘E’s being ‘Effective, Efficient, Easy, Empower, and Equity’ calls for an accountable, transparent and developed face of a globally recognized welfare state. In this direction, we are adopting a highly collaborative approach and addressing challenges like fraud, deceit, financial misplacement and alike, which are hindering the inclusive growth of India. Inter-alia, where fraud is considered as one of the critical ailments, which not only holdup the corporate organizations where it has been conducted, rather it shakes the entire economy sometimes with temporary effects and sometimes with permanent ones, it has always been the priority of growing economies including India to detect, prevent and regulate the menace of fraud in the larger interest of the nation. Due to many white-collar scam and crime in India has questioned the credibility of the financial institutions. In this selection of timely detection, prevention and regulation over corporate fraud and reference to due investigation, Forensic Audit is having an imperative role in assisting the corporates for maintaining efficiency and merit. On the larger parameters, Forensic audit as tool-mix of accounting and investigation is serving all the five E’s of good governance and make the corporates to grow and develop on the parameters of being Effective, Efficient, Easy, Empower, and Equity’. The methodology employed in the study was purely exploratory library-based research. This is based on an in-depth review of relevant and current literature on fact in issues. The findings reveal that forensic auditing is so relevant in today’s corporate world. The relationship that exists between them is linking financial accounting and auditing. Forensic accounting academics emphasize the need for forensic accounting education. However, little is known about whether forensic accounting education has unintended consequences and the literature is quiet on this issue. This gap in the forensic accounting literature is addressed in this article. Further, this review addresses a thought-provoking issue on whether all fraud cases should be given equal investigative priority.